The interface between language appropriation and sign language for deaf people - Andreis-Witkoski, Silvia (2019)
This paper approaches language appropriation by the deaf, pointing out the relevance of the role of Libras in their familiar, scholastic, and social interactions. The discussions are based on Vygotsky’s social-historic theory, according to which the development of language happens when boosted by human interactions. From that theoretical perspective, questions were raised on the effects of privation from Sign Language in deaf children, a gap that stops them from reaching a similar development to that of hearing children because they have no access to a full language. In addition to the need for a deaf child to have access to a Sign Language since a young age, we also point out the importance of nurture in bilingual familiar, scholastic, and social environments for the child to have quality interactions, promoting the full appropriation of language and other correlate developments.